Strengthening Social Relationship at Pande Clan in Improving the Implementation of Hindu Religious Teaching - Kembarawan, I Gusti Komang (International Journal of Psychosocial Rehabilitation, 2020)
This research is intended to conduct an analysis of the strengthening of social relations in the Pande clan related to the improvement of Hindu religious life in Mataram city. This research is focused on the religious social movements carried out by the Pande clan as part of an effort to build unity within the internal Pande clan. The formulation of the problem that this research is relating to the background, impact, and meaning of strengthening social relations among the Pande clan. The research method used in this research is descriptive qualitative. The results showed that the background of the realization of social relations among the Pande clan was related to the awareness to remember kawitan (ancestors) in accordance with what was mandated in bhisama (ancestral spiritual messages) and implement it in daily life, namely tightening the kinship between those who were in a line descendants of the Pande clan. In this regard, the idea emerged to unite themselves as the Maha Semaya Warga Pande (MSWP), as was done by their relatives in Bali. The impact of strengthening social relations among the Pande clans was twofold, namely positive impacts and negative impacts. The positive impact of strengthening social ties tends to remember each other’s brotherhood, which in turn can create a harmonious life among the Pande clans. The negative impact caused by the existence of polarization with other clans. The meaning of strengthening social relations among the Pande clan, such as the meaning of solidarity, religious meaning, cultural meaning, and the meaning of education.